Toward delay mitigation in Iraqi construction projects: Evaluating the causes and the implications - Ali Mohammed Ali Naji Al-Attabi (Ain Shams Engineering Journal, 2025)
Construction projects in Iraq often experience delays due to political instability, economic constraints, and administrative inefficiencies. While several studies have identified the causes of these delays, a comprehensive analysis evaluating their significance and broader implications is lacking. This study addresses this gap by analyzing 74 delay causes and 9 implications using the Relative Importance Index and Cronbach’s alpha. The results show that 59% of the causes are major, with incompetent contractors ranked highest, while 41% are minor. The causes were categorized into nine groups, with owner-related issues being the most significant. The implications were ranked, with quality reduction, time and cost overruns, and declining public trust in the government at the top. Other impacts include psychological stress among citizens, disputes, litigation, total abandonment, and arbitration. This study provides a prioritization framework and practical recommendations for delay mitigation in Iraq and serves as a reference for other post-conflict or developing regions.